Analisis Optimalisasi Perencanaan Produksi Nata De Coco pada PT. Keong Nusantara Abadi Natar Lampung Selatan - Osalia Masya Suci Putri (Journal on Education, 2023)
Keong Nusantara Abadi Natar South Lampung was founded in 1983 by producing canned snails. Then, in 1994 this company developed to become a producer of various food and beverage products under the Wong Coco trademark. One of the products is Nata De Coco. The problem in this research is that the production planning for the 360 gram Nata De Coco bag product is not optimal. This research aims to find out whether PT. Keong Nusantara Abadi Natar South Lampung has carried out optimal production planning for Nata De Coco and has provided considerations to the company regarding optimal production planning. The method used is forecasting and the analytical tool used is linear regression. Based on the results of data analysis calculations, the total production of Nata De Coco for 2022 is 13,324 bags or higher than the 2021 production plan of 8,031 bags. From these production results, it was found that the highest production fell in January with a total monthly production planning of 2,439 bags, while the lowest production results fell in November with a production planning result value of 568 bags.